2015
DOI: 10.1002/jctb.4669
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of NO2 absorption using sodium sulfite in a spray tower

Abstract: BACKGROUND: Wet flue gas desulfurization combined with ozone is a promising technology which could remove NOx effectively. However, there are few reports focusing on simulations of the absorption process of NO 2 in a spray tower. A computational fluid dynamics model including chemical absorption was developed to simulate the absorption process of NO 2 . Simulations of different cases were executed to explore the influences of operating conditions. RESULTS: The errors between predicted and experimental values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…The interactions between nitrogen and sulfur are highly dependent on the pH level due to the dissociative reaction . At pH values ≥7, SO 3 2– is the dominant form, and reaction creates a potential route for NO 2 hydrolysis Reaction has been studied experimentally, and it has a significantly higher reaction rate than reaction . This interaction between S­(IV) and NO 2 (aq) makes the simultaneous absorption of NO 2 and SO 2 an effective process under alkaline conditions.…”
Section: Chemistrymentioning
confidence: 99%
“…The interactions between nitrogen and sulfur are highly dependent on the pH level due to the dissociative reaction . At pH values ≥7, SO 3 2– is the dominant form, and reaction creates a potential route for NO 2 hydrolysis Reaction has been studied experimentally, and it has a significantly higher reaction rate than reaction . This interaction between S­(IV) and NO 2 (aq) makes the simultaneous absorption of NO 2 and SO 2 an effective process under alkaline conditions.…”
Section: Chemistrymentioning
confidence: 99%
“…Other S compositions besides SO3 2− and SO4 2− account for about 4% to 9% in the reaction system. Besides the above-mentioned nitrogen-sulfur compounds, Chen et al [32] and Zhuang et al [32,33] thought that the sulfite radicals could be formed by the reaction between NO2 and sulfite, the sulfite radicals could undergo either recombination or reaction with oxygen. By comparing Figure 4 with Figure 5, it can be seen that the amount of other S compositions is much lower than that of other Similarly, the calculated TS t is also more than the sum of detected SO 3 2− and SO 4 2− , as shown in Figure 5.…”
Section: Equilibrium Analysis Of Nand S Compositionsmentioning
confidence: 99%
“…Other S compositions besides SO 3 2− and SO 4 2− account for about 4% to 9% in the reaction system. Besides the above-mentioned nitrogen-sulfur compounds, Chen et al [32] and Zhuang et al [32,33] thought that the sulfite radicals could be formed by the reaction between NO 2 and Appl. Sci.…”
Section: Equilibrium Analysis Of Nand S Compositionsmentioning
confidence: 99%
“…In Figure a simplified schematic of the reaction paths possible when both SO 2 (g) and NO x (g) are present and in contact with an aqueous phase is shown. SO 2 absorption in water is equilibrium-controlled and leads to the formation of bisulfite and sulfite according to reactions and , respectively Absorption of NO 2 in water takes place according to either reactions or , depending on the presence of NO and the pH level. Nitrite, N­(III), is inherently unstable, especially under acidic conditions, and it can decompose into NO and NO 2 Several studies have shown that S­(IV) is efficient at hydrolyzing NO 2 (aq) at a high rate according to reaction . The SO 3 2– may also be oxidized by O 2 following reaction . In experiments, it was found, as previously mentioned, that the oxidation of S­(IV) progresses at a much higher rate than what is explained by reactions and alone. Nash proposed that a radical-initiated chain of reactions was initiated by reaction and rather progressed through reaction where a sulfite radical was formed.…”
Section: Introductionmentioning
confidence: 99%